Prescott's microbiology - Willey, Joanne M.; Sherwood, Linda; Woolverton, Christopher J. (McGraw-Hill, 2011)
The themes of microbial evolution, ecology, and diversity continue to be integrated throughout the Eighth Edition. The most up-to-date information to maintain accurate descriptions of structures and processes, as well as provide exciting recent discoveries to illustrate essential points, has been added. Illustrations and photos feature three-dimensional renditions and bright, attractive colors! The art program also